The Effect Of Using Jigsaw Technique On Students’ Vocabulary Ability At Smp Swasta Kartika 1-2 Medan - Nita Cindy Siregar; Christy Noverina Girsang (Journal of English Education and Teaching, 2020)
The title of this research is The Effect of Using Jigsaw Technique On Students’ Vocabulary Ability. This research aimed to know how the effect of using jigsaw technique on students’s vocabulary ability at SMP Kartika 1-2 Medan. In this research, the subjects of this research were VII-1 and VII-2’s class with 62 students, VII-1 consist of 31 students called an experimental group and VII-2 consist of 31 students called a control group. This research was a quantitative research. The mean score of the pre test in experimental group was 39,45, the mean score of the post test was 75,90, the mean score of the pre test in control group was 53,41 and the mean score of the post test was 53,93. It concluded that using jigsaw technique is effective and significantly effect to improved students’ vocabulary ability. It proved by the obtained score of T-test, the T-test showed that T-observe was higher than T-table ( 25,53 > 0,05). It meant that Ha was accepted and H0 was rejected.